ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI AIR MINUM DALAM KEMASAN JESSLYN DI PEKANBARU - Linsen '; Rahmita budiartiningsih; Jahrizal ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was carried out on the bottled water industry Jesslyn namely PT. Tirta Emas Kemasindo located in the city of the new week. The purpose of this study was to determine the factors that influence the production of bottled drinking water Jesslyn and what factors are more dominant influence on the production of bottled drinking water in the city pekanbaru Jesslyn.The analytical method used quantitative descriptive method by using multiple regression analys function coob-douglass. The results show that the magnitude of the coefficient of determination (R2) by there independent variables it is 0.743 give meaning to the influence of labor, technology and capital to the production of bottle water Jesslyn PT. Tirta Emas Kemasindo of 74,3%, while the rest 26,7 %Factors that favor the production of bottle water jesslyn not addressed in this study. Test partial regression (t test) showed that the independent variables studied, namely labor (X1), raw materials (X2) positive effect on the dependent variableis the production of the bottle water jesslyn while technology (X3) positive effect was not significant to the production of drinking water in packs of bottled water Jesslyn PT. Tirtya Emas Kemasindo new week. Factors are more dominant influence on the production of bottled water is power Jesslyn.Keywords : Production Jesslyn bottled water, labor, raw materials and technology